Immunization against nucleus pulposus antigens to accelerate degenerative disc disease in a rabbit model - Bonilla, Andres F.; Sikes, Katie J.; Burton, Lindsey H.; Chow, Lyndah; Kurihara, Jade; Santangelo, Kelly; Dow, Steven W.; Easley, Jeremiah T. (Frontiers in Veterinary Science, 2024)
Low back pain poses a significant societal burden, with progressive intervertebral disc degeneration (IDD) emerging as a pivotal contributor to chronic pain. Improved animal models of progressive IDD are needed to comprehensively investigate new diagnostic and therapeutic approaches to managing IDD. Recent studies underscore the immune system's involvement in IDD, particularly with regards to the role of immune privileged tissues such as the nucleus pulposus (NP) becoming an immune targeting following initial disc injury. We therefore hypothesized that generating an active immune response against NP antigens with an NP vaccine could significantly accelerate and refine an IDD animal model triggered by mechanical puncture of the disc. To address this question, rabbits were immunized against NP antigens following disc puncture, and the impact on development of progressive IDD was assessed radiographically, functionally, and histologically compared between vaccinated and non-vaccinated animals over a 12-week period. Immune responses to NP antigens were assessed by ELISA and Western blot. We found that the vaccine elicited strong immune responses against NP antigens, including a dominant ~37 kD antigen. Histologic evaluation revealed increases IDD in animals that received the NP vaccine plus disc puncture, compared to disc puncture and vaccine only animals. Imaging evaluation evidenced a decrease in disc height index and higher scores of disc degeneration in animals after disc punctures and in those animals that received the NP vaccine in addition to disc puncture. These findings therefore indicate that it is possible to elicit immune responses against NP antigens in adult animals, and that these immune responses may contribute to accelerated development of IDD in a novel immune-induced and accelerated IDD model.